HIV and AIDS in the state of Paraná, Brazil, 2007-2022: trends and spatiotemporal distribution - Rafaela Marito Montanha; Thamy Barbara Gioia; Antônio Carlos Vieira Ramos; Natalia Marciano de Araujo Ferreira; Miguel Angel Fuentealba Torres; Rosângela Aparecida Pimenta; Gilselena Kerbauy; Ricardo Alexandre Arcêncio; Flávia Meneguetti Pieri (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: The aim of this study was to analyze the spatiotemporal evolution of the incidence rates of human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) in the state of Paraná, Brazil. Methods: An ecological study with an analytical component of time series analysis was conducted in the state of Paraná from 2007 to 2022. The data source was the Notifiable Diseases Information System. To study the trend, the Prais-Winsten generalized linear regression model was used by decomposing the time series, and for spatial analysis, the Moran's index was applied. Results: The total sample consisted of 50,676 HIV/AIDS records. The incidence rate showed an increasing trend, with an average growth of 2.14% [95% confidence interval - 95%CI 1.16-3.13] per month. From 2007 to 2014 and from 2015 to 2022, the average number of cases in the state was 105.64 and 159.20 per 100,000 inhabitants, respectively, with significant variation among municipalities. Spatial clusters of high risk persisted in the metropolitan region, the capital, and coastal areas, and a new cluster was observed in the northern region of the state. Conclusion: The incidence rates of HIV/AIDS showed an upward trend over time. The number of cases varied considerably in some municipalities, especially in the coastal region. Spatial analysis revealed geospatial patterns of high risk in the main metropolitan areas of Paraná: Curitiba (including the coastal area), Londrina, and Maringá, which share characteristics such as a high degree of urbanization and ongoing economic development.